Creation and Efficiency Determination of a Modular Refrigeration and Air Conditioning Practice Set According to the National Skilled Labor Standards - Chuenchomnakjad, Saksit; Promseenong, Prataep; Sema, Prida (Journal of Technical and Engineering Education, 2024)
The objectives of this research were (1) to create a modular refrigeration and air- conditioning training kit in accordance with the National Skill Standards; (2) to determine teaching efficiency using modular refrigeration and air-conditioning practice kits; and (3) to study students’ satisfaction with teaching and learning from the use of modular refrigeration and air conditioning training units in accordance with the National Skill Standards. The collected data were from a sample group of high school students: 21 students using a specific selection method. The tools used to collect data consisted of 1) the refrigeration and air conditioning training kit created by the researchers; 2) the quality assessment of the refrigeration training system; 3) the knowledge test and performance assessment; and 4) the questionnaire of students’ satisfaction with the refrigeration and air- conditioning training set. The results showed that the quality was very good ( = 4.68, S.D. = 0.40) in accordance with the National Skill Standards. The efficiency of teaching using modular cooling and air-conditioning practice was 84.56 and post-test score was 82.37 percent, which was higher than the prescribed criteria for effectiveness at 80/80. The students’ satisfaction with teaching and learning from the use of modular cold and air-conditioning training kits was at a highest level ( = 4.61, S.D. = 0.51) of the National Skill Standards. Lastly, the results of the National Skill Standards students who have learned using the modular refrigeration and air conditioning training set created accounted for 95.24 percent.